Providing information at the initial consultation to patients with low back pain across general practice, chiropractic and physiotherapy - a cross-sectorial study of Danish primary care - Morsø, Lars; Lykkegaard, Jesper; Andersen, Merethe Kirstine; Hansen, Anders; Stochkendahl, Mette Jensen; Madsen, Simon Dyrløv; Christensen, Berit Schiøttz (Scandinavian journal of primary health care, 2022)
Clinical guidelines for managing low back pain (LBP) emphasise patient information, patient education and physical activity as key components. Little is known about who actually receives information. This study investigates to what extent information at the first consultation with general practitioner (GP), chiropractor (DC) and physiotherapist (PT) in Danish primary care is provided to patients with LBP. This cross-sectorial study was conducted as a prospective survey registration of LBP consultations at the three primary health care professions in Denmark. Clinicians ticked off a paper survey chart during or after consultations with patients who visited the clinic for LBP (Approval number: ID # 11.220). 33 GPs, 43 DCs and 61 PTs registered first-time consultations. The primary outcome was provision of information, overall and across care settings. The overall proportion of patients provided with information was 72%, but this varied among professions (GP, 44%; DC, 76%; and PT, 74%). Provision of information increased to 78% if patients had increased emotional distress or back-related leg pain below the knee. The strongest association with provision of information was having two or three signs of elevated distress (OR 2.58 and 5.05, respectively, p= 0.00) or physical disability (OR 2.55, p= 0.00). In more than a quarter of first-time consultations, patient information was not provided. Large variation in providing information was found across the settings. The proportion provided with information increased for sub-populations having elevated distress or back-related leg pain below the knee. Key Points Clinical guidelines recommend patient information, patient education and physical activity for managing low back pain (LBP)  * Information is not provided in more than a quarter of first-time consultations in Danish primary care settings that manage these patients. * Information increased for the sub-populations having elevated distress and back-related leg pain below the knee. * The conducted primary care surveys monitored clinical activity and illustrated variations in provision of information.